2015
DOI: 10.1186/s12864-015-1868-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of long intergenic non-coding RNAs (lincRNAs) provides new insight into viral diseases in honey bees Apis cerana and Apis mellifera

Abstract: BackgroundLong non-coding RNAs (lncRNAs) are a class of RNAs that do not encode proteins. Recently, lncRNAs have gained special attention for their roles in various biological process and diseases.ResultsIn an attempt to identify long intergenic non-coding RNAs (lincRNAs) and their possible involvement in honey bee development and diseases, we analyzed RNA-seq datasets generated from Asian honey bee (Apis cerana) and western honey bee (Apis mellifera). We identified 2470 lincRNAs with an average length of 1011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 68 publications
5
65
0
Order By: Relevance
“…For example, lncRNA plays pivotal roles in controlling the stressresponse in plants including Populus [80] and wheat [30]. Jayakodi et al identified 15 long intergenic non-coding RNAs (lincRNAs) showing significant differential expression between sacbrood virus (SBV)-infected and uninfected Apis cerana, and further confirmed the expression of 11 lincRNAs using RT-qPCR [38]. In this work, the expression levels of 111 and 146 lncRNAs were observed to significantly alter in N.…”
Section: Lncrnassupporting
confidence: 64%
See 1 more Smart Citation
“…For example, lncRNA plays pivotal roles in controlling the stressresponse in plants including Populus [80] and wheat [30]. Jayakodi et al identified 15 long intergenic non-coding RNAs (lincRNAs) showing significant differential expression between sacbrood virus (SBV)-infected and uninfected Apis cerana, and further confirmed the expression of 11 lincRNAs using RT-qPCR [38]. In this work, the expression levels of 111 and 146 lncRNAs were observed to significantly alter in N.…”
Section: Lncrnassupporting
confidence: 64%
“…Utilizing transcriptome sequencing, Jayakodi et al [38] identified 1514 long intergenic non-coding RNAs (lincRNAs) in A. mellifera and 2470 lincRNAs in Apis cerana, most of which had a tissue-specific expression pattern. More recently, Chen et al [39] predicted a variety of lncRNAs, miRNAs and mRNAs during the ovary activation, oviposition inhibition and oviposition recovery processes; and they further found 73 differentially expressed genes and 14 differentially expressed lncRNAs (DElncRNAs) located in the QTL region, which may be candidate genes responsible for ovary size and oviposition.…”
Section: Introductionmentioning
confidence: 99%
“…Although lncRNAs are widely identified in some insect species with the application of RNA‐seq technology (Etebari et al ., ; Jayakodi et al ., ; Jenkins et al ., ; Legeai & Derrien, ; Xiao et al ., ; Chen et al ., ; Wu et al ., ), the information about lncRNAs in the silkworm is relatively rare. A previous study suggested that nine silk gland‐enriched ncRNAs may be involved in the development of silk gland and fibroin synthesis (Li et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, many lncRNAs are essential for normal development and survival (Anderson et al, 2016;Goff et al, 2015;Sauvageau et al, 2013). Developmentally expressed lncRNAs have also been identified in C. elegans (Nam and Bartel, 2012), Drosophila and other insects (Brown et al, 2014;Chen et al, 2016a;Jayakodi et al, 2015;Jenkins et al, 2015;Wu et al, 2016;Young et al, 2012), and echinoderms (Mu et al, 2016). In contrast, the systematic investigation of lncRNAs in non-bilaterian metazoans has been lagging behind ( Fig.…”
Section: Animal Long Non-coding Rnasmentioning
confidence: 99%
“…However, lncRNAs are rapidly evolving and exhibit poor primary sequence similarity between species; orthologues are difficult to identify (Ulitsky, 2016), thus precluding a detailed understanding of their functionality in an evolutionary developmental framework. In fact, while the role of lncRNAs in the regulation of developmental gene activity appears to be widespread amongst animals (Bråte et al, 2015;Brown et al, 2014;Chen et al, 2016a;Forouzmand et al, 2016;Gaiti et al, 2015;Jayakodi et al, 2015;Jenkins et al, 2015;Mu et al, 2016;Nam and Bartel, 2012;Necsulea et al, 2014;Pauli et al, 2012;Sauvageau et al, 2013;Tan et al, 2013;Ulitsky et al, 2011;Wu et al, 2016;Young et al, 2012), only a handful of lncRNAs have thus far been shown to function in evolutionarily divergent animals, mostly restricted to bilaterians (Grant et al, 2012;Heard et al, 1999;Migeon et al, 1999;Ulitsky et al, 2011).…”
Section: Introductionmentioning
confidence: 99%